Which Nature Experience Do Pupils Aged 14/15 and 17/18 Year Gain? An Empirical Cross-Sectional Study in the State of Bavaria (South Germany) to the Theme of Nature Experience of the Year 2007 - Zecha, Stefanie (Journal of Geography Education, 2010)
This study investigates in nature experiences of 14/15 and 17/18 year high school (Gymnasium) students in Bavaria (South Germany). In particular, the author was interested in a) the level of outdoor experiences of each group, b) the influence of independent factors as gender and environmental behavior at home on nature experience and c) the relation between outdoor experience and environmental knowledge, readiness to act and actual environmental behavior. The author used a standardized questionnaire. The results showed a significant age effect on the intensity of nature experiences. The older group achieved in nearly all dimensions of nature experiences higher values. The influence of the size of location and of gender seemed to be higher in the younger group. The older adolescents did not have the same expectations of nature experience as the younger group. There is a very high relation between nature experiences and environmental knowledge, readiness to act and actual environmental behavior. The article concludes with the results being discussed in respect of environmental education at university and school.